A Systematic Literature Review on Concret Media: Application to Mathematics Learning - Tria Mardiana; Sardin; Wijayanto, Sukma (EDUPEDIA Publisher, 2023)
The application of media in learning can facilitate the transfer of information. The purpose of this study is to analyze the application of concrete media to learning Mathematics. Concrete media is one of the media that is easy to obtain as well as visual thinking for students. Concrete media can provide real and meaningful direct learning experiences for students. This Systematic Literature Review focuses on peer-reviewed journals and data obtained from the Mendeley database using specific criteria to analyze Concrete Media in Mathematics Learning from 2018-2022. There were 40 articles analyzed in this study which were indexed by SINTA and Google Scholar. Based on the research, through the Systematic Literature Review the results were obtained that the application of concrete media in learning Mathematics can increase student activity and learning outcomes, as well as affect the ability to solve mathematical problems. An important finding in this research is, the application of concrete media makes the preparation of media procurement simpler and easy. This is because concrete media can be obtained in the surrounding environment and does not need to take a long time to procure. This can summarize the teacher's preparation time if they want to use the media in the Mathematics learning activities carried out.